The Effectiveness of English Enrichment Program in Odd Semester on Improving English Language Skills to UIB Students - Leil Badrah Zaki; Vanesse Goh; Hendra Nugraha (English Learning Innovation, 2025)
This study aims to analyze the effectiveness of the program run by A university Language Center, namely the English Enrichment Program (EEP) in improving the English language skills of the students. The effectiveness can be seen through the teaching methods applied by lecturers which are proven to be effective in helping students and the effect of EEP classes on improving students' English language skills. The participants in this study were 2 lecturers and 49 students who participated in EEP classes in the odd semester 2023/2024. This research applied mixed methods, with questionnaires and semi-structured interviews to collect research data adapted from Hoffmann (2019) research. The results showed that the teaching methods applied, namely the Grammar-Translation method and also by giving tips and trick to answer the question, successfully developed students' abilities in reading and listening sessions. The results also proved that although the implementation of EEP classes still found some weaknesses such as internet connection problem due to online learning which causes lack of understanding and interaction between teacher and students, and several meetings which is not enough time for TOEIC preparation. However, the majority of students thought that the effectiveness of EEP still helped them in developing English language skills. Therefore, the results of this study highlight indicate that structured enrichment programs, such as the English Enrichment Program (EEP), can effectively complement formal English instruction, especially when they utilize well-designed and pedagogically sound teaching strategies.